1997
DOI: 10.20885/psikologika.vol2.iss2.art1
|View full text |Cite
|
Sign up to set email alerts
|

Child-Rearing Practices and Temperament of Children: Are They Really Determinants of Children's Aggression?

Abstract: Very few studies on children's aggression conducted in the Eastern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the 90 samples from 80 studies (124 027 children), the correlation was small but significant ( r , 0.11; 95% CI, 0.10-0.12) (Figure 2). The Egger test result provided evidence that studies with smaller sample sizes had more extreme effect sizes, and the funnel plot showed asymmetry (eFigure 1 in the Supplement), indicating possible publication bias and/or small-study effects. There was evidence of significant between-study heterogeneity ( Q , 729.78; P < .001; I 2 = 87.80); therefore, moderators were explored (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the 90 samples from 80 studies (124 027 children), the correlation was small but significant ( r , 0.11; 95% CI, 0.10-0.12) (Figure 2). The Egger test result provided evidence that studies with smaller sample sizes had more extreme effect sizes, and the funnel plot showed asymmetry (eFigure 1 in the Supplement), indicating possible publication bias and/or small-study effects. There was evidence of significant between-study heterogeneity ( Q , 729.78; P < .001; I 2 = 87.80); therefore, moderators were explored (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“… 28 They are also described as having few opportunities to develop initiative and dependence on parents may be encouraged. 29 Less emphasis is placed on respectful obedience among rural farming families, with greater tolerance for self-reliance and responsibility among children. 27…”
Section: Context: the Thrive By Five International Program In Indonesiamentioning
confidence: 99%